Turbulence slapping technique effect on the multiphase flow behavior in pipeline - Saw, Chin Hooi (2010)
The experiment is concerned with an experimental investigation of the drag reduction in two phase (solid-liquid) turbulent flow over the mechanical chain. A circulating loop for the fluid flow with 0.0381 inside diameter of pipe is set up. The testing length of the system is 1.5m.Wall shear stress reduction performance has been investigated experimentally for various design geometry surfaces including a replica of bent consisting of stainless steel model scales. Attempts to optimize the net drag reduction by varying the design geometry and alignment are also discussed. The study indicated that the presence of turbulence can be reduced under the influence of mechanical chain. But, the effect of mechanical chain decreases as Reynolds Number (Re) increases. The results show that a substantial drag reduction can be achieved by this mechanical chain in aqueous media.